2012
DOI: 10.1111/j.1540-6210.2012.02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Equities and Inequities in Practice: Street‐Level Workers as Agents and Pragmatists

Abstract: Street‐level workers’ judgments, decisions, and actions touch on questions of social equity, a dominant theme of H. George Frederickson's deep contributions to public administration scholarship. Based on empirical work, the authors question the dominant implementation‐control‐discretion narrative and suggest an alternative framing based on the concepts of agency and pragmatic improvisation. Street‐level workers are often conservers of institutional norms and practices, but their work surfaces tensions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
227
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(238 citation statements)
references
References 21 publications
5
227
0
6
Order By: Relevance
“…As a result, motivational patterns observed in this study might be specific to several scope conditions, such as the presence of a multilevel legal context with ambiguity between national and EU obligations, the high level of discretion in the German administrative setting and the normatively laden policy field that requires considerable client interactions at the frontline. Yet, from the street-level bureaucracy literature, we can expect that other client-intensive and normatively laden fields comparable to migration, such as social policies, might reveal similar motivational mechanisms as found in this study (Maynard-Moody and Musheno 2012). The study might be less representative for more technical fields of EU law which may trigger less normative motivations.…”
Section: Resultsmentioning
confidence: 41%
See 2 more Smart Citations
“…As a result, motivational patterns observed in this study might be specific to several scope conditions, such as the presence of a multilevel legal context with ambiguity between national and EU obligations, the high level of discretion in the German administrative setting and the normatively laden policy field that requires considerable client interactions at the frontline. Yet, from the street-level bureaucracy literature, we can expect that other client-intensive and normatively laden fields comparable to migration, such as social policies, might reveal similar motivational mechanisms as found in this study (Maynard-Moody and Musheno 2012). The study might be less representative for more technical fields of EU law which may trigger less normative motivations.…”
Section: Resultsmentioning
confidence: 41%
“…Second, in line with the street-level literature (Lipsky 1980;Maynard-Moody and Musheno 2012) and studies on migration management (Ellermann 2006;Eule 2014;Jordan et al 2003), the implementers investigated in this study were creative and flexible in their use of legal tools. While the limited literature on practical EU implementation has treated administrations as yet another source for non-compliance (Versluis 2007) or ignored the street-level of EU implementation (Treib 2014), this study has shown that lower level implementers are surprisingly aware of the multilevel legal context in which they operate.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…While discretion addresses "the notion of decision-making within the structure of rules" (Feldman 1992, p. 164), this new citizen-agent narrative does not limit worker decision making to the application of existing law and rules. Maynard-Moody and Musheno (2012) suggest that concepts of agency and pragmatic improvisation better describe worker decision-making. The citizen-agent narrative identifies cases of workers going above and beyond procedural guidelines to help or harm citizens based on judgments about identity, behavior, character, and worthiness (Maynard-Moody & Musheno, 2003).…”
Section: Administrative Decision-makingmentioning
confidence: 99%
“…In our specific case, we might have explored the incentives and sanctions in the system or whether valvemen faced conflicting mandates from different ''principals" (see Gailmard & Patty, 2012;Shapiro, 2005;Maynard-Moody & Musheno, 2012).…”
mentioning
confidence: 99%